Mortality in adult-onset and elderly-onset IBD: a nationwide register-based cohort study 1964–2014. Issue 3 (15th May 2019) - Olén, Ola; Askling, Johan; Sachs, Michael C; Neovius, Martin; Smedby, Karin E; Ekbom, Anders; Ludvigsson, Jonas F
Abstract : Objectives: To examine all-cause and cause-specific mortality in adult-onset and elderly-onset IBD and to describe time trends in mortality over the past 50 years. Design: Swedish nationwide register-based cohort study 1964–2014, comparing mortality in 82 718 incident IBD cases (inpatient and non-primary outpatient care) with 10 times as many matched general population reference individuals (n=801 180) using multivariable Cox regression to estimate HRs. Among patients with IBD, the number of participants with elderly-onset (≥60 years) IBD was 17 873. Results: During 984 330 person-years of follow-up, 15 698/82 718 (19%) of all patients with IBD died (15.9/1000 person-years) compared with 121 095/801 180 (15.1%) of reference individuals, corresponding to an HR of 1.5 for IBD (95% CI=1.5 to 1.5 (HR=1.5; 95% CI=1.5 to 1.5 in elderly-onset IBD)) or one extra death each year per 263 patients. Mortality was increased specifically for UC (HR=1.4; 95% CI=1.4 to 1.5), Crohn's disease (HR=1.6; 95% CI=1.6 to 1.7) and IBD-unclasssified (HR=1.6; 95% CI=1.5 to 1.8). IBD was linked to increased rates of multiple causes of death, including cardiovascular disease (HR=1.3; 1.3 to 1.3), malignancy (HR=1.4; 1.4 to 1.5) and digestive disease (HR=5.2; 95% CI=4.9 to 5.5). Relative mortality during the first 5 years of follow-up decreased significantly over time. Incident cases of 2002–2014 had 2.3 years shorter mean estimated life span than matched comparators. Conclusions: Adult-onset and elderly-onset patients with UC, Crohn's disease and IBD-unclassified were all at increased risk of death. The increased mortality remained also after the introduction of biological therapies but has decreased over time.